2018
DOI: 10.1080/14789949.2018.1439990
|View full text |Cite
|
Sign up to set email alerts
|

Group size, misinformation and unanimity influences on co-witness judgements

Abstract: Group size, misinformation and unanimity influences on co-witness judgments Original CitationMojtahedi, Dara, Ioannou, Maria and Hammond, Laura (2018) Group size, misinformation and unanimity influences on co-witness judgments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…Results indicated that, compared with the control group, participants who discussed the event with misleading cowitnesses were significantly more likely to make the same false blame attribution as them. The findings are in line with previous research on blame conformity, which have found that participants will conform to their cowitness's misinformation when attempting to determine which person from an incident was at fault for the crime (e.g., Mojtahedi et al, ; Thorley, ). The increase in false blame attributions within the misinformation condition can be explained by the informational influence model.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Results indicated that, compared with the control group, participants who discussed the event with misleading cowitnesses were significantly more likely to make the same false blame attribution as them. The findings are in line with previous research on blame conformity, which have found that participants will conform to their cowitness's misinformation when attempting to determine which person from an incident was at fault for the crime (e.g., Mojtahedi et al, ; Thorley, ). The increase in false blame attributions within the misinformation condition can be explained by the informational influence model.…”
Section: Discussionsupporting
confidence: 90%
“…Much of the research on memory conformity has typically shown that participants can be influenced into incorrectly reporting both peripheral details from an event (such as the colour of the offender's clothing; see Gabbert, Memon, Allan, & Wright, 2004) and information more central to the incident (such as the number of perpetrators involved; see Wright, Self, & Justice, 2000). More recent research has demonstrated that participants can also be influenced by their cowitnesses when attempting to attribute blame-a form of memory conformity, otherwise referred to as blame conformity (see Mojtahedi, Ioannou, & Hammond, 2017;Mojtahedi, Ioannou, & Hammond, 2018a;Mojtahedi, Ioannou, & Hammond, 2018b;Thorley, 2015;Thorley & Rushton-Woods, 2013). Thorley (2015) demonstrated the effects of blame conformity in a study which showed participants footage of a crime taking place, before providing them with a misleading statement from a previous witness which blamed an innocent bystander for committing the crime.…”
Section: Introductionmentioning
confidence: 99%
“…This means training such as Mental Health First Aid Training can be utilised across forces in order to address any stigmatising attitudes and also meet the needs of the custody staff. Given the strong emphasis on improving current interviewing procedures (Gibert & Mojtahedi, 2018;Mojtahedi, Ioannou, & Hammond, 2019;Mojtahedi, Ioannou, & Hammond, 2018a;Mojtahedi, Ioannou, & Hammond, 2018b;Mojtahedi, Ioannou, & Hammond, 2017a;Mojtahedi, Ioannou, & Hammond, 2017b ), a fruitful direction for future research, currently being pursued by the current authors, is to explore the effects of stigmatising attributions on police officers' approaches to interviewing witnesses experiencing mental ill health.…”
Section: Resultsmentioning
confidence: 99%
“…Keeping in line with the fundamental aims of investigative psychology, another fruitful direction for future research that could enhance the investigative and legal processes associated with crimes of child sexual abuse would be to focus on improving the way witness/victim statements are recorded and evaluated. Research has repeatedly demonstrated the ease for distorted and unreliable information to be recorded during interviews (see McWilliam & Mojtahedi, ; Mojtahedi, Ioannou, & Hammond, , , ).…”
Section: Resultsmentioning
confidence: 99%